Origin of Archean Pb isotope variability through open-system Paleoarchean crustal anatexis - Hartnady, Michael; Kirkand, C.L.; Johnson, S.P.; Smithies, Hugh; Doucet, Luc; Mole, D.R. (2024)
Lead isotopic data imply that thorium and uranium were fractionated from one another in Earth’s early history; however, the origin of this fractionation is poorly understood. We report new in situ Pb isotope data from orthoclase in 144 granites sampled across the Archean Yilgarn craton (Western Australia) to characterize its Pb isotope variability and evolution. Granite Pb isotope compositions reveal three Pb sources, a mantle-derived Pb reservoir and two crustal Pb reservoirs, distinguished by their implied source 232Th/238U (κPb). High-κPb granites reflect sources with high 232Th/238U (~4.7) and are largely co-located with Eoarchean–Paleoarchean crust. The Pb isotope compositions of most granites, and those of volcanic-hosted massive sulfide (VHMS) and gold ores, define a mixing array between a mantle Pb source and a Th-rich Eoarchean–Paleoarchean source. Pb isotope modeling indicates that the high-κPb source rocks experienced Th/U fractionation at ca. 3.3 Ga. As Th/U fractionation in the Yilgarn craton must have occurred before Earth’s atmosphere was oxygenated, subaerial weathering cannot explain the apparent differences in their geochemical behavior. Instead, the high Th/U source reflects Eoarchean–Paleoarchean rocks that experienced prior high-temperature metamorphism, partial melting, and melt loss in the presence of a Th-sequestering mineral like monazite. Archean Pb isotope variability thus has its origins in open-system high-temperature metamorphic processes responsible for the differentiation and stabilization of Earth’s continental crust.